Availability, production, and consumption of crops biofortified by plant breeding: current evidence and future potential - Saltzman, Amy; Birol, Ekin; Oparinde, Adewale; Andersson, Meike S.; Asare-Marfo, Dorene; Diressie, Michael T.; González, Carolina; Lividini, Keith; Moursi, Mourad; Zeller, Manfred (Wiley, 2017)
Biofortification is the process of increasing the density of vitamins and minerals in a crop through plant breeding—using either conventional methods or genetic engineering—or through agronomic practices. Over the past 15 years, conventional breeding efforts have resulted in the development of varieties of several staple food crops with significant levels of the three micronutrients most limiting in diets: zinc, iron, and vitamin A. More than 15 million people in developing countries now grow and consume biofortified crops. Evidence from nutrition research shows that biofortified varieties provide considerable amounts of bioavailable micronutrients, and consumption of these varieties can improve micronutrient deficiency status among target populations. Farmer adoption and consumer acceptance research shows that farmers and consumers like the various production and consumption characteristics of biofortified varieties, as much as (if not more than) popular conventional varieties, even in the absence of nutritional information. Further development and delivery of these micronutrient‐rich varieties can potentially reduce hidden hunger, especially in rural populations whose diets rely on staple food crops. Future work includes strengthening the supply of and the demand for biofortified staple food crops and facilitating targeted investment to those crop–country combinations that have the highest potential nutritional impact.